Displaying Fel d1 on virus-like particles prevents reactogenicity despite greatly enhanced immunogenicity: a novel therapy for cat allergy. - Schmitz, N; Dietmeier, K; Bauer, M; Maudrich, M; Utzinger, S; Muntwiler, S; Saudan, P; Bachmann, M (2009)
Allergen-specific desensitization is the only disease-modifying therapy currently available for the treatment of allergies. These therapies require application of allergen over several years and some may induce life-threatening anaphylactic reactions. An ideal vaccine for desensitization should be highly immunogenic and should alleviate allergic symptoms upon few injections while being nonreactogenic. We describe such a vaccine for the treatment of cat allergy, consisting of the major cat allergen Fel d1 coupled to bacteriophage Qbeta-derived virus-like particles (Qbeta-Fel d1). Qbeta-Fel d1 was highly immunogenic, and a single vaccination was sufficient to induce protection against type I allergic reactions. Allergen-specific immunoglobulin G antibodies were shown to be the critical effector molecules and alleviated symptoms by two distinct mechanisms. Although allergen-induced systemic basophil degranulation was inhibited in an FcgammaRIIb-dependent manner, inhibition of local mast cell degranulation in tissues occurred independently of FcgammaRIIb. In addition, treatment with Qbeta-Fel d1 abolished IgE memory responses upon antigen recall. Despite high immunogenicity, the vaccine was essentially nonreactogenic and vaccination induced neither local nor systemic anaphylactic reactions in sensitized mice. Moreover, Qbeta-Fel d1 did not induce degranulation of basophils derived from human volunteers with cat allergies. These data suggest that vaccination with Qbeta-Fel d1 may be a safe and effective treatment for cat allergy.